PUBLIC ACCOUNTABILITY PADA STREET LEVEL BUREAUCRAT LAYANAN COMMAND CENTER 112 KOTA SURABAYA - Dinda Prasetyawati Putri Suryono, Difanda; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Command Center 112 is well known as an emergency service program in Surabaya City with an effective and efficient system that has won several awards. This achievement prompted this research to obtain adequate information about the street level bureaucrats of Command Center 112. The purpose of this research is to describe the portrait of accountability through the meaning of roles to the orientation of street level bureaucrat accountability involved in the 112 Command Center service of Surabaya City. The researcher attempted to solve the problem with a descriptive qualitative research method using interview, observation, and literature study techniques. The results of this research showed that street level bureaucrats carry out their accountability through two types of accountability, namely Public-Administrative Accountability and Participatory Accountability, thus increasing job pressure and encouraging the occurrence of role conflict dilemmas. The conflict experienced by street level bureaucrats in this research is a policy vs societal conflict. Furthermore, accountability orientation can be reviewed through its actions in overcoming dilemmas that lead to centrist policies. Centric policies are also referred to as center-based policies which uphold applicable service operational standards. This can be observed through the actions of emergency telephone receivers in carrying out their duties to prioritize compliance with the tasks contained in policy rules rather than the wishes of the community. Recommendations that can be given include affirming the SOP for the community as a reporter, providing measures and understanding of emergencies, adding service infrastructure, and updating data every month.